This is ear hustle: unflinching stories of everyday prison life - Poor, Nigel (Crown, 2022)
Part I: let's do this -- Earlonne -- Nigel -- Ear hustle -- Part II: we're gonna take you inside -- Prison 101 -- Objects -- Alliances -- Memory -- Family -- Three strikes -- Part III: inside out -- Commutation -- With and without -- Locked out -- Epilogue: Inked -- Postscript: this guy here.